Broadband single molecule SERS detection designed by warped optical spaces. Issue 1 (December 2018) - Mao, Peng; Liu, Changxu; Favraud, Gael; Chen, Qiang; Han, Min; Fratalocchi, Andrea; Zhang, Shuang
Abstract Engineering hotspots is of crucial importance in many applications including energy harvesting, nano-lasers, subwavelength imaging, and biomedical sensing. Surface-enhanced Raman scattering spectroscopy is a key technique to identify analytes that would otherwise be difficult to diagnose. In standard systems, hotspots are realised with nanostructures made by acute tips or narrow gaps. Owing to the low probability for molecules to reach such tiny active regions, high sensitivity is always accompanied by a large preparation time for analyte accumulation which hinders the time response. Inspired by transformation optics, we introduce an approach based on warped spaces to manipulate hotspots, resulting in broadband enhancements in both the magnitude and volume. Experiments for single molecule detection with a fast soaking time are realised in conjunction with broadband response and uniformity. Such engineering could provide a new design platform for a rich manifold of devices, which can benefit from broadband and huge field enhancements. In standard SERS the probability for the molecules to reach tiny hotpot regions is low. Here, the authors introduce an approach based on warped spaces that offers a strategy to manipulate hotspots of metallic nanostructures, resulting in large broadband enhancements in both the magnitude and the volume size.